Administrative aspects in the book “Nuzhat al-Muqaltain fi Akhbar al-Dawlatyn” by Ibn al-Tuwair (d. 617 AH/1220 AD) (Journal of the College of Basic Education, 2025)
Ibn al-Tuwair is considered one of the most reliable historians in writing the history of the Fatimid state in Egypt, which ruled for nearly two hundred years (395-567 AH/969-1171 AD). His credibility is evident in his clear assessment of the importance of the administrative factor in shaping historical events. The book "Nuzhat al-Muqallatain" is an important work that addresses a significant aspect of the administrative Fatimid state in Egypt. This importance lies in its impact on political and military life. Ibn al-Tuwair sheds light on the administrative aspect of the Fatimids in Egypt. Moreover, Egypt witnessed prosperity during the years of Fatimid rule, expanding into various regions. In this research, we will shed light on the administrative aspect of the Fatimid state through this book, which includes several axes.